2005
DOI: 10.1002/cbdv.200590020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Antibacterial and Hemolytic Activity of Shorter‐ and Longer‐Chain β‐, α,β‐, and γ‐Peptides, and of β‐Peptides from β2‐3‐Aza‐ and β3‐2‐Methylidene‐amino Acids Bearing Proteinogenic Side Chains – A Survey

Abstract: The antibacterial activities of 31 different beta-, mixed alpha/beta-, and gamma-peptides, as well as of beta-peptides derived from beta2-3-aza- and beta3-2-methylidene-amino acids were assayed against six pathogens (Enterococcus faecalis, Staphylococcus aureus, Streptococcus pneumoniae, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa), and the results were compared with literature data. The interaction of these peptides with mammalian cells, as modeled by measuring the hemolysis of human e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…The genes are most similar to a V8 protease, which can cleave the heavy chain of human immunoglobulin classes in vitro. In 64% of the isolates the s pl operon was present and no obvious role in virulence was demonstrated in intraperitoneally injected rats [22], [29].…”
Section: Discussionmentioning
confidence: 98%
“…The genes are most similar to a V8 protease, which can cleave the heavy chain of human immunoglobulin classes in vitro. In 64% of the isolates the s pl operon was present and no obvious role in virulence was demonstrated in intraperitoneally injected rats [22], [29].…”
Section: Discussionmentioning
confidence: 98%
“…Our group47,48 as well as those of Gellman49 and Seebach50 independently showed that β-peptides capable of forming amphiphilic 14- or 12-helices had potent antimicrobial activity. Oligomers with lengths of 10-15 residues that achieved an appropriate hydrophilic/lipophilic balance were selective for killing bacteria vs. mammalian cells.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, first studies on the stability of ␤-peptides in vivo have shown that virtually no degradation was observed when such peptides were administered to rats (42,43). Some ␤-peptides possess antimicrobial activities (4,5,25,38), bind to the human somatostatin receptor (12,21), function as inhibitors of human immunodeficiency virus type 1 replication (39), and inhibit p53-hDM2 interaction (18). Cationic ␤-peptides cross bacterial and mammalian cell membranes and can be considered a new group of cell-penetrating peptides (13,26,31).…”
mentioning
confidence: 99%